Osteoblast derived extracellular vesicles induced by dexamethasone: A novel biomimetic tool for enhancing osteogenesis in vitro - Zhang, Xing; Zhao, Qun; Zhou, Nan; Liu, Yu; Qin, Kang; Buhl, Eva Miriam; Wang, Xinhong; Hildebrand, Frank; Balmayor, Elizabeth R.; Greven, Johannes (Frontiers in Bioengineering and Biotechnology, 2023)
Extracellular vesicles (EVs) are newly appreciated communicators involved in intercellular crosstalk, and have emerged as a promising biomimetic tool for bone tissue regeneration, overcoming many of the limitations associated with cell-based therapies. However, the significance of osteoblast-derived extracellular vesicles on osteogenesis has not been fully established. In this present study, we aim to investigate the therapeutic potential of extracellular vesicles secreted from consecutive 14 days of dexamethasone-stimulated osteoblasts (OB-EVDex) to act as a biomimetic tool for regulating osteogenesis, and to elucidate the underlying mechanisms. OB-EVdex treated groups are compared to the clinically used osteo-inductor of BMP-2 as control. Our findings revealed that OB-EVDex have a typical bilayer membrane nanostructure of, with an average diameter of 178 ± 21 nm, and that fluorescently labeled OB-EVDex were engulfed by osteoblasts in a time-dependent manner. The proliferation, attachment, and viability capacities of OB-EVDex-treated osteoblasts were significantly improved when compared to untreated cells, with the highest proliferative rate observed in the OB-EVDex + BMP-2 group. Notably, combinations of OB-EVDex and BMP-2 markedly promoted osteogenic differentiation by positively upregulating osteogenesis-related gene expression levels of RUNX2, BGLAP, SPP1, SPARC, Col 1A1, and ALPL relative to BMP-2 or OB-EVDex treatment alone. Mineralization assays also showed greater pro-osteogenic potency after combined applications of OB-EVDex and BMP-2, as evidenced by a notable increase in mineralized nodules (calcium deposition) revealed by Alkaline Phosphatase (ALP), Alizarin Red Alizarin Red staining (ARS), and von Kossa staining. Therefore, our findings shed light on the potential of OB-EVDex as a new therapeutic option for enhancing osteogenesis.